Atypical presentation of clay shoveler's fracture: A case report and literature review - Owolabi IJ; Onuoha KM; Alade OA; Shobode MA (International Journal of Spine Research - Peertechz Publications, 2020)
Clay shoveler's fracture causes disruption of the spinous processes at C6 to T3 spinal vertebrae. This is a case report of an atypical clay shoveler's fracture from Babcock university teaching Hospital ,Ogun-state, Nigeria. It involved a 62-year-old male travelling in the south-western region of Nigeria who was invloved in a Road traffic accident and presented with pain at the posterior aspect of the neck. X-ray and 3D oriented CT scan confirmed the fractures with lateral views being the most favored. Classical Clay shoveler's fracture usually has no neuromuscular deficit since it is a stable fracture and involves only the posterior spinal column based on the Denis classification for 3 column concept for stable and unstable fractures of the spine. When a fracture involves the spinolaminar line it's proximity to the spinal cord and risk of neurological deficit must be adequately ruled out. This report evaluates the mechanism of injury, treatment given and prognosis of the patient involved.